Performance feedback enhances test-potentiated encoding - Ludowicy, Petra; Paz-Alonso, Pedro M.; Lachmann, Thomas; Czernochowski, Daniela (Frontiers in Behavioral Neuroscience, 2023)
Introduction Long-term memory retention is enhanced after testing compared to restudying (testing effect). Notably, memory retrieval further improves when correct-answer feedback is provided after the retrieval attempt (test-potentiated encoding–TPE). Methods To evaluate whether explicit positive or negative feedback further enhances memory performance beyond the effect of TPE, in two experiments additional explicit positive or negative performance-contingent feedback was presented before providing correct-answer feedback. After an initial exposure to the full material, 40 participants learned 210 weakly associated cue-target word pairs by either restudying or testing (Experiment 1). Depending on the accuracy of the retrieval attempt, the tested word pairs were followed by positive or negative performance feedback (50%) or no feedback (50%). Irrespective of the type of repetition, trials were followed by a restudy opportunity. Participants returned to perform a final cued-recall test (Day 2). Results Final test results replicated the testing effect (better memory performance for tested compared to restudied items). Explicit performance feedback in addition to correct-answer feedback increased retrieval performance, but only on Day 2. This pattern of results was replicated in Experiment 2 in an independent sample of 25 participants. To assess the specific effects of learning history, we also examined retrieval accuracy and reaction times during repetition cycles: Explicit feedback improved retrieval for material successfully encoded in the initial study phase (consistent positive feedback) as well as for material learned during the repetition phase (mixed positive and negative feedback). Discussion Performance feedback improves learning beyond the effects of retrieval practice and correct-answer feedback, suggesting that it strengthens memory representations and promotes re-encoding of the material.